Prevalence and antimicrobial susceptibility pattern of thermophilic Campylobacter spp. isolated from ovine carcasses and faeces in Ethiopia - Hailemariam, S.; Feleke, A.; Szonyi, Barbara; Fries, R.; Baumann, M.P.O.; Grace, Delia (Addis Ababa University, 2015)
The foodborne thermophilic Campylobacter species are considered to be the leading cause of human gastroenteritis worldwide with emerging antimicrobial resistant strains. Consumption of raw or undercooked meat is an important source for zoonotic infection. A cross-sectional study was conducted on sheep destined for slaughter at a slaughterhouse in Addis Ababa to determine the prevalence of thermophilic Campylobacter spp. A total of 160 carcass swabs and 160 rectal swabs were bacteriologically examined from which 21 (13.1%) and 12 (7.5%) thermophilic Campylobacter spp. were isolated, respectively. Biochemical test results of the carcass isolates indicated 12 (57.1%) to be C. jejuni, 6 (28.6%) C. coli and 3 (14.3%) C. lari. Similar examination of abattoir environment pool samples of eight sampling days revealed 7 (87.5%) to be positive for the thermophilic Campylobacter spp. None of the wash water samples were positive for the bacteria. Antimicrobial susceptibility pattern test towards twelve antimicrobials using standard disc diffusion method revealed higher resistance (38.1%) for amoxicillin-clavulanic acid and kanamycin (38.1%) followed by streptomycin, oxytetracycline and compound sulphonamide (33.3% each). Most isolates were susceptible to ceftriaxone and clindamycin (4.8% each) and to a lesser degree to erythromycin (9.5%). Multidrug resistance was observed in 52.4% of the isolates examined. Isolation of thermophilic Campylobacter spp., with higher isolation rate for C. jejuni, the primary cause of human campylobacteriosis, from sheep meat and the existence of resistant isolates highlight the potential threat to public health. Therefore, implementation of Campylobacter prevention and control strategies from farm production to consumption of sheep meat are crucial.